1994
DOI: 10.3109/09513599409058032
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentration, urinary excretion and renal clearance of L-carnitine during pregnancy: a reversible secondary L-carnitine deficiency

Abstract: Plasma concentration, urinary excretion and renal clearance of free, total and esterified L-carnitine were monitored monthly in 14 women during the last 6 months of pregnancy and 1 month after delivery. Plasma concentration and renal clearance measured 1 month after delivery overlapped with normal values for females of comparable age, and were considered the reference values for further comparisons. Plasma concentration of free, total and esterified L-carnitine decreased during pregnancy, reaching values as lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
2
9
0
3
Order By: Relevance
“…The present study agrees with other studies ((Bargen-Lockner et al, 1981;Cederblad et al, 1985Cederblad et al, , 1986Genger et al, 1988;Marzo et al, 1994;Schoderbeck et al, 1995;Cho et al, 2003) in showing that plasma carnitine concentrations in women markedly decline during pregnancy. In our study, plasma Table 3 Concentration of g-butyrobetaine and 6-N-trimethyllysine in plasma of women receiving either a L-carnitine supplement (500 mg per day) or a placebo from the 12th week of gestation until delivery at various time points Table 2 Concentration of total carnitine, free carnitine and carnitine esters in plasma of women receiving either a L-carnitine supplement (500 mg per day) or a placebo from the 12th week of gestation until delivery at various time points carnitine concentration at delivery in the placebo group was approximately 40% lower than that at week 12 of pregnancy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study agrees with other studies ((Bargen-Lockner et al, 1981;Cederblad et al, 1985Cederblad et al, , 1986Genger et al, 1988;Marzo et al, 1994;Schoderbeck et al, 1995;Cho et al, 2003) in showing that plasma carnitine concentrations in women markedly decline during pregnancy. In our study, plasma Table 3 Concentration of g-butyrobetaine and 6-N-trimethyllysine in plasma of women receiving either a L-carnitine supplement (500 mg per day) or a placebo from the 12th week of gestation until delivery at various time points Table 2 Concentration of total carnitine, free carnitine and carnitine esters in plasma of women receiving either a L-carnitine supplement (500 mg per day) or a placebo from the 12th week of gestation until delivery at various time points carnitine concentration at delivery in the placebo group was approximately 40% lower than that at week 12 of pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…Physiologically, plasma carnitine concentrations are strongly controlled by the renal excretion of carnitine (Rebouche and Seim, 1998). It has been found that urinary excretion of carnitine even declines during pregnancy and paralleled plasma carnitine concentrations (Cederblad et al, 1986;Marzo et al, 1994). Therefore, an increased renal excretion of carnitine can be ruled out as a possible reason for the low plasma carnitine concentrations during late pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in total carnitine is mainly caused by a decrease in free carnitine (Schoderbeck et al 1995) and is thought to be the consequence of a reduced rate of carnitine biosynthesis, possibly because of an inadequate iron status (Keller et al 2009) or because of a low availability of precursors for carnitine (Ringseis et al 2010). Interestingly, one study reported a complete normalization of plasma carnitine one month after delivery (Marzo et al 1994), and our finding of low-normal free carnitine 16 days after delivery may reflect a partial normalization to concentrations often seen in patients with MCADD.…”
Section: Discussionmentioning
confidence: 99%
“…Although all of those studies involve children, and our mouse studies document NSC derangements in imposed in mid-gestation, the clinical data are nonetheless consistent with the carnitine deficiency hypothesis. In that regard, multiple studies document significant decreases in maternal serum carnitine levels during pregnancy that approach pathologically low levels (52)(53)(54)(55)(56)(57)(58)(59). Interestingly, that decline in carnitine levels commences at the onset of mid-gestation (12 weeks, 58,59), a window that corresponds to the one where we interfere with carnitine synthesis and fatty acid ␤-oxidation in our mouse in utero electroporation experiments (34).…”
Section: Asbmb Award Article: Neural Stem Cell Carnitine Malnutritionmentioning
confidence: 71%